Integrating the Certainty of Response Index (CRI) with Environmental Literacy and Creative Thinking Indicators to Analyze Misconceptions in Renewable Energy Learning among Vocational High School Students - Budiati, Idha; Patonah, Siti; Hayat, Muhammad Syaipul (Unnes Science Education Journal, 2025)
This study investigates vocational high school students’ misconceptions about renewable energy concepts using the Certainty of Response Index (CRI) and examines their relationship with environmental literacy and creative thinking skills. A descriptive quantitative design with a diagnostic approach was employed. The instruments consisted of a three-tier multiple-choice test for environmental literacy and a two-tier essay test for creative thinking, both validated through Aiken’s V (V = 0.75–1.00; valid–highly valid) and piloted prior to implementation. CRI analysis revealed substantial misconceptions, particularly in energy transition (67%) and marine energy utilization (50%). Students demonstrated stronger understanding of concrete topics (e.g., fossil energy impact, IoT integration) but struggled with abstract or unfamiliar content. Creative thinking performance was weakest in originality and elaboration, with errors linked to limited contextual exposure and insufficient inquiry-based learning opportunities. Notably, high confidence often accompanied incorrect reasoning, indicating entrenched misconceptions. Statistical analysis indicated a moderate positive correlation between environmental literacy and creative thinking (r = 0.56, p < 0.05). These findings highlight the potential of integrating CRI-based diagnostics with STEAM–SDGs-oriented, project-based, and contextual learning to address misconceptions, enhance environmental literacy, and develop students’ creative capacity. Such strategies are critical to bridging the knowledge–action gap and preparing students to tackle sustainable energy challenges in the era of the green economy.